Negotiating identities in contemporary Africa: gender, religion, and ethno-cultural identities - Falola, Toyin; Mbah, Emmanuel M. (Lanham, Maryland: Lexington Books, 2023)
"This edited volume provides an interdisciplinary and balanced discussion on the changing dynamics of identities in Africa, with a focus on gender, ethno-cultural, and religious identity"--
Introduction: Negotiating Identities in Contemporary Africa: Gender, Religion, and Ethno-cultural Identities / by Emmanuel M. Mbah and Toyin Falola -- Chapter 1: Sowing in the Wind: Girls' Education in Kenya's Bungoma County / by Namulundah Florence -- Chapter 2: Gendered Political Institutions and Women's Career Identity Construction / by Wakil Ajibola Asekun -- Chapter 3: To Have or Not to Have: An African Perspective on Childlessness / by Namulundah Florence -- Chapter 4: Gender and Initiation Rites in Ejagham Land of Cameroon / by Victor Ntui Atom -- Chapter 5: Restoring Gender Knowledge in Kenya's Mau Mau War: New Methods and Perspectives / by Mickie Mwanzia Koster -- Chapter 6: Gender Inequality in the Peace Building Process during the Anglophone Crisis in Cameroon / by Primus Fonkeng -- Chapter 7: From Hapless Victims to Helpful Collaborators? The Contradictions of Boko Haram Female Suicide Bombers (FSBs) in Nigeria, 2009-2019 / by Femi Adegbulu -- Chapter 8: A Comparative Study of the Influence of Modernization on Traditional Gender Roles of Men and Women in Lagos and Ogun States, Nigeria / by Tolu Ogunleye -- Chapter 9: Ethnocentrism, Democratization and Nation Building in Africa: The Nigerian Experience / by Steve A Iyayi -- Chapter 10: Identity Dynamics in the Southern Tier of the Cameroon-Nigeria Frontier / by Victor Ntui Atom -- Chapter 11: Redefining Cultural Identity in Nigeria through Dramatic and Theatrical Arts / by Adedoyin Aguoru -- Chapter 12: "I never knew I was a Negro until I came to America." Black Identity, Diasporic Consciousness, and Nigerian Ambivalence to Pan-Africanism / by Ajibola A. Abdulrahman -- Chapter 13: Sidis in India, and of India, too? An Exploratory Study into the Identity of the African Diaspora in the Western Indian State of Gujarat / by Pradeep Mallik -- Appendix A: 2016 Kenya Certificate of Secondary Education Results of Select Bungoma County Boys' Secondary/High Schools -- Appendix B: 2016 Kenya Certificate of Secondary Education Results of Select Bungoma County Girls' Secondary/High Schools -- Appendix C: 2016 Kenya Certificate of Secondary Education Results of Select Bungoma County Mixed Secondary/High Schools in Bungoma County -- Appendix D: 2016 Kenya Certificate of Secondary Education Results of the Two National Schools in Bungoma County. -- Appendix E: 2016 Kenya Certificate of Secondary Education results of Extra-County High Schools in Bungoma County. -- Appendix F: 2017 Kenya Certificate of Secondary Education Results of Bumula Constituency, Secondary/High Schools in Bungoma County.
Includes bibliographical references and index.
Keywords: Women -- Africa, Sub-Saharan -- Social conditions; Sex role -- Africa, Sub-Saharan.; Ethnicity -- Africa, Sub-Saharan.; Africa, Sub-Saharan -- Social conditions -- 21st century